Formula Optimization of Rosemary (Rosmarinus officinalis L.) Extract-loaded Film-forming Spray using Box-Behnken Design - Aulia, Ridha Nurul; Akmal, Tubagus (Journal of Experimental and Clinical Pharmacy (JECP), 2025)
Film-forming sprays are practical and effective in creating a protective film on wounds that evenly distributes active ingredients. Rosmarinic acid in rosemary has antioxidant and anti-inflammatory properties, helping to accelerate wound healing by enhancing macrophage and lymphocyte proliferation and reducing inflammation. This study aims to determine the optimal formulation of a film-forming spray using xanthan gum as a film-forming agent, propylene glycol as a plasticizer, and ethanol as a penetration enhancer. Optimization was carried out using the Box-Behnken design in Design Expert-13, focusing on viscosity, spray diameter, spray angle, area, density, and theoretical film thickness. The optimal base and extract formulas were evaluated for stability over 28 days at room temperature using GraphPad Prism-10. The ideal formula contained 0.1% xanthan gum, 3.6% propylene glycol, and 40% ethanol, with a desirability score of 0.943. The confirmation results showed no significant difference between actual and predicted values, validating the model. The optimal formula had a viscosity of 100 ± 0.00 cps, a spray diameter of 4.52 ± 0.06 cm, a spray angle of 65.70 ± 0.31°, an area of 16.02 ± 0.43 cm², a density of 0.908 ± 0.00 g/ml, and a theoretical film thickness of 0.007 ± 0.00 cm. This formula was then used as the base for the rosemary extract FFS. Stability tests showed that the addition of extracts significantly affected viscosity, spray diameter, spray angle, area, and theoretical film thickness (p<0.05), while density was unaffected (p>0.05). The study’s limitation is the lack of in vivo testing to confirm the formulation's effectiveness in promoting wound healing and its antimicrobial properties.